Real-world data on Empagliflozin and Dapagliflozin use in patients with HEART failure: The RED-HEART study - Kocabas, Umut; Ergin, Isil; Yavuz, Veysel; Altin, Cihan; Kaplan, Mehmet; Oztekin, Gulsum Meral Yilmaz; Turk, Ugur Onsel (Oxford Univ Press, 2025)
Aims We aimed to determine the use of sodium-glucose cotransporter 2 inhibitors (SGLT2is) and to identify clinical factors associated with their use in patients with heart failure (HF) in a real-life setting. Methods Real-world data on Empagliflozin and Dapagliflozin use in patients with HEART failure: The RED-HEART study is a multicentre, cross-sectional and observational study that included HF patients in the outpatient setting regardless of ejection fraction from 19 cardiology centres between August 2023 and December 2023. Results The study population consisted of 1923 patients with HF, predominantly men (61.2%), with a median age of 66 (range: 19-101) years. Overall, 925 patients (48.1%) were receiving SGLT2is. Among the study population, 22.1% had HF with preserved ejection fraction, 21.5% had HF with mildly reduced ejection fraction, 56.4% had HF with reduced ejection fraction and the use of SGLT2is was 42.0%, 47.9% and 50.6% in each group, respectively (P = 0.012). The use of SGLT2is was 76.6% in patients with HF and diabetes, 19.8% in patients with HF and chronic kidney disease and 26.8% in patients without diabetes and chronic kidney disease (P < 0.001). Higher education level [odds ratio (OR): 1.80; 95% confidence interval (CI): 1.06-3.05; P = 0.027], higher household income (OR: 3.46; 95% CI: 1.27-9.42; P = 0.015), New York Heart Association functional class IV (OR: 2.72; 95% CI: 1.16-6.35; P = 0.021), diabetes (OR: 9.42; 95% CI: 6.72-13.20; P < 0.001), the use of angiotensin receptor-neprilysin inhibitors (ARNis) (OR: 4.09; 95% CI: 2.39-7.01; P < 0.001), the use of mineralocorticoid receptor antagonists (MRAs) (OR: 2.02; 95% CI: 1.49-2.75; P < 0.001), the use of loop diuretics (OR: 1.62; 95% CI: 1.18-2.22; P = 0.003) and the use of thiazide diuretics (OR: 1.72; 95% CI: 1.30-2.29; P < 0.001) were independently associated with the use of SGLT2is. Conversely, atrial fibrillation (OR: 0.63; 95% CI: 0.45-0.88; P = 0.008), chronic kidney disease (OR: 0.53; 95% CI: 0.37-0.76; P = 0.001), the use of dihydropyridine calcium channel blockers (OR: 0.68; 95% CI: 0.48-0.98; P = 0.042) and the use of statins (OR: 0.67; 95% CI: 0.49-0.91; P = 0.010) were independently associated with the non-use of SGLT2is. Conclusions The RED-HEART study provided comprehensive real-world data about implementing SGLT2is in patients with HF. These results suggest that there is a need for organized action and close collaboration between healthcare providers to improve the implementation of SGLT2is, especially in patients with HF with preserved ejection fraction and chronic kidney disease.
Keywords: guideline; heart failure; sodium-glucose cotransporter 2 inhibitors